Profiling Academic Research on Language Teacher Identities - Yi-Fen Liu (Asociación Colombiana de Profesores de Ingles, 2022)
Within the field of TESOL, language teacher identity (LTI) has been the focus of a myriad of studies in the previous two decades. Researchers need to trace back in order to move forward, it is an essential step towards a comprehensive understanding of what has been done in LTI research. This review article provides an overall literature review on conceptual approaches of how identity is defined and perceived in the context of recent history. It is then followed by an analysis of dominant trends on recent studies of Language Teacher Identity to profile what, why, when, and who constitute seminal works in LTI research by tracing scholarly literature from 1975 to the present. A dataset retrieved and analyzed from Scopus was further correlated using Vantage Point software. The findings not only revealed the conceptual approaches, dominant trends, and methodological development in LTI research, but also identified the underexplored areas in transnational teacher identities, teacher educator identities, and online teacher identities, which provided implications for future LTI research directions.